Microplastics in human urine: Characterisation using μFTIR and sampling challenges using healthy donors and endometriosis participants - Jeanette M. Rotchell; Chloe Austin; Emma Chapman; Charlotte A. Atherall; Catriona R. Liddle; Timothy S. Dunstan; Ben Blackburn; Andrew Mead; Kate Filart; Ellie Beeby; Keith Cunningham; Jane Allen; et al. (Ecotoxicology and Environmental Safety, 2024)
Microplastics (MPs) are found in all environments, within the human food chain, and have been recently detected in several human tissues. The objective herein was to undertake an analysis of MP contamination in human urine samples, from healthy individuals and participants with endometriosis, with respect to their presence, levels, and the characteristics of any particles identified. A total of 38 human urine samples and 15 procedural blanks were analysed. MPs were characterised using μFTIR spectroscopy (size limitation of 5 μm) and SEM-EDX. In total, 123 MP particles consisting of 22 MP polymer types were identified within 17/29 of the healthy donor (10 mL) urine samples, compared with 232 MP particles of differing 16 MP polymer types in 12/19 urine samples from participants with endometriosis. Healthy donors presented an unadjusted average of 2589 ± 2931 MP/L and participants with endometriosis presented 4724 ± 9710 MP/L. Polyethylene (PE)(27%), polystyrene (PS)(16%), resin and polypropylene (PP)(both 12%) polymer types were most abundant in healthy donor samples, compared with polytetrafluoroethylene (PTFE) (59%), and PE (16%) in samples from endometriosis participants. The MP levels within healthy and endometriosis participant samples were not significantly different. However, the predominant polymer types varied, and the MPs from the metal catheter-derived endometriosis participant samples and healthy donors were significantly smaller than those observed in the procedural blanks. The procedural blank samples comprised 62 MP particles of 10 MP polymer types, mainly PP (27%), PE (21%), and PS (15%) with a mean ± SD of 17 ± 18, highlighting the unavoidable contamination inherent in measurement of MPs from donors. This is the first evidence of MP contamination in human urine with polymer characterisation and accounting for procedural blanks. These results support the phenomenon of transport of MPs within humans, specifically to the bladder, and their characterisation of types, shapes and size ranges identified therein.